Perfect enemies the religious right, the gay movement, and the politics of the 1990s - Gallagher, John; Bull, Chris (Crown Publ., 1996)
A political war is raging in the United States between two groups once considered radical, even marginal, by most Americans: the religious right and the gay movement. Perfect Enemies reveals why this conflict has moved to the center of political debate and become a pivotal issue in elections at all levels. In Perfect Enemies, Chris Bull and John Gallagher trace the origins and growth of both groups from the seminal year of 1969, when the Stonewall Riots ushered in the modern gay rights movement and when Pat Robertson and Jerry Falwell embarked on direct political action to bring strict biblical interpretation to bear on public policy. The skillful grassroots organizational efforts of both movements, based on a mutual demonization of each side by the other, resulted in growing political clout that developed under the radar of mainstream political commentators - and exploded upon the scene in a series of bitter and, to most Americans, bewildering political conflicts